The Impact of Diagnostic Status on Quality of Life in Irritable Bowel Syndrome - Cassar, Gillian Eleanor; Youssef J, George; Knowles, Simon R; Moulding, Richard; Austin, David (Turkish Journal of Gastroenterology, 2021)
Background: The aim of the study was to examine the impact of diagnostic status (i.e., having a clinical diagnosis of irritable bowelsyndrome (IBS) or being symptomatic but undiagnosed on quality of life (QoL)). We also examined whether the relationships betweenQoL and variables such as symptom frequency, pain catastrophizing, visceral sensitivity, and psychological distress are moderated bydiagnostic status.Methods: The online sample comprised 404 participants (Mage = 33.59, SD = 12.43), of which 98 had been diagnosed with IBS and306 were symptomatic but undiagnosed.Results: The findings suggest that even after adjusting for symptom frequency, those diagnosed with IBS experience poorer QoL, relativeto those without a diagnosis. Moreover, there was evidence that the relationship between specific QoL domains (namely, sex, foodavoidance, and health worry) and psychological variables (namely, pain catastrophizing, and depression) was moderated by diagnosticstatus.Conclusion: The results indicate that diagnostic status in relation to IBS has psychological implications for QoL outcomes distinctfrom symptom frequency, age, and gender. This highlights a substantial gap in our current understanding of how a diagnosis of IBS canimpact the lives of those suffering from IBS symptomology and calls into question the intended purpose of diagnosis.